Anterior mediastinal collision tumor of type AB thymoma and adenocarcinoma: a case report - Kang, Zhongqin; Xu, Rong; Wang, Weiya; Yan, Keyu; Liao, Yi; Zhang, Lizhi (Frontiers in Oncology, 2025)
Collision tumors are defined as the coexistence of two or more histologically distinct tumor types at the same anatomical site. Mediastinal collision tumors constitute an exceptionally rare subtype of these lesions. Clinically and radiologically, the preoperative diagnosis is particularly difficult due to their complex pathological composition and nonspecific manifestations. Misdiagnoses are common in clinical practice, even with preoperative needle biopsy. Radiologic identification of collision tumors is essential to ensure comprehensive sampling for guiding appropriate treatments. Herein, we report an extremely rare case of mediastinal collision tumor diagnosed by contrast-enhanced chest computed tomography (CT), with pathology confirming type AB thymoma and well-differentiated adenocarcinoma (likely of malignant foregut cyst origin). This case report aims to raise awareness of this rare tumor and to discuss the imaging features based on a systematic review of the literature.